BIOECOLOGY OF EREMERUS M.BIEB OF KOHITANG FLORA (Academicia Globe: Inderscience Research, 2022)
The Kohitang ridge is located in the south-western part of the Pamir-Alay mountain . Administratively, it belongs to the territory of Sherabad district of Surkhandarya region. The Kohitang Range is bounded on the north by the Tangidara River and Suvsiztog. The eastern and southern territories are connected by the Kelif-Sherabad plains. The western slope of the Kohitang Range is the territory of the Republic of Turkmenistan.